OPTIMALISASI KEBUGARAN MELALUI PENDEKATAN INOVATIF PJOK MENYONGSONG GENERASI SEHAT DAN AKTIF - Suharti; Hendri Mulyadi; M. Torero Rigel Centeury; Moh. Ifkhal Sianto; Yohanes Selvianus Tola; Singgih Prastawa (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
Physical Education, Sports and Health (PJOK) has a strategic role in shaping a healthy, active and productive generation. This article discusses innovative approaches in the implementation of PJOK as an effort to optimize students' physical fitness. The main focus of the research is the integration of interactive learning methods, the use of technology, and the adjustment of fitness programs according to individual needs. The results of the analysis show that innovative approaches, such as the use of fitness apps, project-based learning, and collaboration between schools and sports communities, are able to increase student participation, understanding of fitness concepts, and awareness of the importance of a healthy lifestyle. Thus, this approach is a strategic solution in addressing the challenge of low fitness levels of the younger generation. This article is expected to be a practical guide for educators and stakeholders in developing PJOK programs that are more relevant, effective, and oriented towards the formation of a healthy and active generation.